An Analysis of English Idioms Found in One Album Of Aerosmith’s - MARSHELA NORARAYA HAREFA (LINGUA LITERA : journal of english linguistics and literature, 2015)
English idioms often appear in different part of speech and variety structures. Understanding the types and structural variations of English idiom can help nonnative speakers recognize how English idioms exist in an oral or written communication. Therefore, this research was done in order to find the types andstructural variations of English idioms in Aerosmith’s song lyrics. The source of the data of this research was Aerosmith’s song lyrics in the album 20 Century Masters: The Millennium Collection: The Best of Aerosmith. It includes twelve song lyrics which are written in English. The writer applied the theory of Cowie (1985) to classify the types of idioms and the theory of Baker (1992) to analyze idiom structural variations. The writer concluded that there are three main classifications of the types of idiom found in Aerosmith’s song lyrics; phrasal idiom, verbal idiom, and sentential idiom. Then, there are five kinds of variations of idiom found in Aerosmith’s song lyrics; by changing the order of the words, deleting a word, adding a word, replacing a word with another, and changing its grammatical structure.